Impacto da osteocalcina na esteroidogenese ovariana - Spricigo, Matheus Colpo (2021)
Osteocalcin, known as bone gamma-carboxy glutamic acid-containing protein (BGLAP), is a small (49-amino-acid) noncollagenous protein hormone secreted by osteoblasts usually reported as a marker of bone formation. More recently, other roles for osteocalcin in insulin secretion and sensibility have been suggested, although its impact on the ovarian steroid secretion remains obscure. Therefore, the present study aims to investigate the presence of osteocalcin receptor (GPCR6A) in the granulosa and theca cells of the bovine ovary and the possible effect of osteocalcin on steroidogenic enzymes. Our results indicate, for the first time, the presence of the osteocalcin receptor GPRC6A in theca cells and testis and its absence or very low expression in the granulosa cells. After treatment with non-carboxylated osteocalcin (100ng/ml), a significant effect size on the key steroidogenic enzymes (CYP17A1, CYP11A1) and protein (STAR) was observed in the first hour (but not 24-hour) only in the presence of co- treatment with luteinizing hormone (LH). Lower doses of non-carboxylated osteocalcin (1ng/ml) were not effective to influence these enzymes. Although limited, our results demonstrate that there appears to be some action of osteocalcin in the first hour after treatment, increasing mRNA expression in key steroidogenic enzymes such as STAR, CYP11A1, and CYP17A1 synergistically with the use of LH (100 ng/ml).